Climate proofing the renewable electricity deployment in Europe - Introducing climate variability in large energy systems models. (May 2021) - Simoes, Sofia G.; Amorim, Filipa; Siggini, Gildas; Sessa, Valentina; Saint-Drenan, Yves-Marie; Carvalho, Sílvia; Mraihi, Hamza; Assoumou, Edi
Abstract: Climate and weather conditions influence energy demand. as well as electricity generation, especially due to the strong development of renewable energy. The changes of the European energy mix, together with ongoing climate change, raise a number of questions on impact on the electricity sector. In this paper we present results for the whole of the European power sector regarding on how considering current and future climate variability affects the results of a TIMES energy system model for the whole European power sector (eTIMES-EU) up to 2050. For each member-state we consider six climate projections to generate future capacity factors for wind, solar and hydro power generation. as well as temperature impact on electricity demand for heating and cooling. These are input into the eTIMES-EU model to assess how climate affects the optimal operation of the power system and if current EU-wide RES and emissions target deployment may be affected. Results show that although at EU-wide level there are no substantial changes, there are significant differences in countries RES deployment (especially wind and solar) and in electricity trade. Highlights: We share insights on including six climate projections in energy models. Climate impacts in wind, solar, hydro capacity factors for EU are estimated. Combined effects for whole of Europe power system are assessed by 2050. Overall there is a significant change in role of solar and wind by considering climate change. There is high uncertainty on direction of effects due to very diverse climate projections.